Integrative Dissection of Novel Lactate Metabolism-Related Signature in the Tumor Immune Microenvironment and Prognostic Prediction in Breast Cancer - Yang, Lu; Tan, Peixin; Sun, Hengwen; Zeng, Zijun; Pan, Yi (Frontiers in Oncology, 2022)
The outcomes of some breast cancer patients remain poor due to being susceptible to recurrence, metastasis and drug resistance, and lactate metabolism has been described as a hallmark of cancer and a contributor to cancer progression and immune escape. Hence, it is worthy of seeking potentially novel biomarkers from lactate metabolism relevant perspectives for this particular cohort of patients. In this context, 205 available lactate metabolism-related genes (LMGs) were obtained by a search of multiple genesets, and the landscape of somatic mutation, copy number variation, and mRNA expression levels was investigated among these genes. Crucially, 9 overall survival-related LMGs were identified through univariate Cox regression analysis in The Cancer Genome Atlas (TCGA) and Molecular Taxonomy of Breast Cancer International Consortium (METABRIC) databases. Subsequently, a prognostic signature, defined as Lactate Metabolism Index (LMI), was established with 5 OS-related LMGs using Least Absolute Shrinkage and Selection Operator (LASSO) Cox hazard regression analysis in TCGA training set, and then validated in two external cohorts (METABRIC and GSE96058). From the comprehensive results, breast cancer patients with high LMI had considerably poorer survival probability across all cohorts, and the degree of clinical features tended to be more severe as the LMI value increased. Furthermore, a prognostic nomogram incorporating LMI, age, and AJCC stage was constructed and demonstrated great prediction performance for OS of breast cancer patients, which was evaluated by the calibration plot and the decision curve analysis. Moreover, the potential effect of different LMI values on levels of immune checkpoints, tumor-infiltrating immune cells, and cytokines were explored ultimately, and patients with higher LMI values might gain an immunosuppressive tumor microenvironment that contributed to immune escape of breast cancer and inferior prognosis. Collectively, all findings in the study indicated the potential prognostic value of LMI in breast cancer, providing further implications for the role of lactate metabolism in breast cancer prognosis, tumor immune microenvironment, and immunotherapy.